2022
DOI: 10.3389/frsen.2022.856903
|View full text |Cite
|
Sign up to set email alerts
|

The Global 2000-2020 Land Cover and Land Use Change Dataset Derived From the Landsat Archive: First Results

Abstract: Recent advances in Landsat archive data processing and characterization enhanced our capacity to map land cover and land use globally with higher precision, temporal frequency, and thematic detail. Here, we present the first results from a project aimed at annual multidecadal land monitoring providing critical information for tracking global progress towards sustainable development. The global 30-m spatial resolution dataset quantifies changes in forest extent and height, cropland, built-up lands, surface wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(152 citation statements)
references
References 42 publications
1
85
0
2
Order By: Relevance
“…For instance, agriculture expanded due to increasing demand for food products in Brazil, Africa, Central Asia, Eastern China and Southeast Asia ( Hu et al., 2021 ). Likewise, Potapov et al. (2022) found that the largest net cropland expansion was in Africa, followed by Asia and South America.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…For instance, agriculture expanded due to increasing demand for food products in Brazil, Africa, Central Asia, Eastern China and Southeast Asia ( Hu et al., 2021 ). Likewise, Potapov et al. (2022) found that the largest net cropland expansion was in Africa, followed by Asia and South America.…”
Section: Resultsmentioning
confidence: 98%
“…While some of the land cover themes can be directly mapped using a single-day satellite images, others may not be directly retrieved from the optical medium resolution data. The incompleteness of the Landsat observation time series decreases map accuracy in a given area with persistent cloud cover ( Potapov et al., 2022 ). Moreover, pixels are acquired at different times and different viewing geometries, under different atmospheric conditions ( Shen et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that these uncertainties will continue with normalized difference vegetation index (NDVI) imagery using satellite technologies that are not supported by ground reality on a global scale. LU/LC algorithms that classify global land cover into different types may not be suitable for producing scientific Assessment of Land Degradation Factors DOI: http://dx.doi.org/10.5772/intechopen.107524 approaches and realistic values [32]. Global and national LU/LC data produced using different approaches are inadequate or inappropriate for land use management and reporting [33,34].…”
Section: Land Use/cover Changesmentioning
confidence: 99%
“…The long-term high resolution (10–30 m) records of Landsat and the recent Sentinel-2 data are now used to derive tree cover loss [ 42 ] and land-cover changes [ 1 , 75 , 103 ], and to improve the mapping of small fires which can result in a doubling of burned area [ 12 ]. These data can be combined with satellite-based biomass maps to estimate biomass carbon changes [ 45 ] as discussed above.…”
Section: Introductionmentioning
confidence: 99%